Design and Calibration of Electron Stack Spectrometer for Diagnosing Hot Electron Temperature in Intense Laser-plasma Interactions - BO Nan1, 2, TIAN Baoxian2, WANG Haoran3, 4, WANG Naiyan2 (Yuanzineng kexue jishu)
The interaction of relativistic intense lasers with matter generates complex plasma environments characterized by extreme conditions, such as high temperatures and densities, which are critical to fields like laser-driven inertial confinement fusion (ICF), high-energy-density physics, and strong-field physics. Accurate diagnosis of the hot electron temperature within these plasmas is essential for understanding energy coupling mechanisms and the spatiotemporal evolution of the plasma. However, the intense electromagnetic pulses (EMPs) and high-flux radiation produced during these interactions pose significant challenges to conventional electronic measurement techniques, often leading to signal saturation or interference. To address these issues, this study introduces the design, construction, and calibration of a passive electron stack spectrometer based on image plate (IP), specifically tailored for diagnosing hot electron temperatures in laser-plasma interactions. The electron stack spectrometer leverages the advantages of IP, including high radiation sensitivity, a wide dynamic range, and reusability, making it suitable for environments with strong EMPs. The spectrometer consists of multiple layers of low-Z absorption materials (e.g., aluminum, titanium, and graphite) interleaved with BAS-SR-type IPs, chosen for their enhanced sensitivity to electrons over gamma rays. The design covers an energy range of 0.2 to 4.0 MeV, aligning with the expected electron energies produced by laser intensities of 1018 to 1020 W/cm2. A collimator and shielding ensure precise measurements by minimizing scattered radiation, and the modular structure allows for accurate alignment with the laser target. Calibration was performed using a monoenergetic electron beam from a 2 MeV radiofrequency superconducting accelerator at Peking University. The experimental setup included a beryllium window for vacuum isolation, an electromagnet that measures the energy of electron beam and a Faraday cup to measure beam charge, with a plastic scintillator detector cross-referencing the electron flux incident on the spectrometer. The response matrix, which characterizes the signal-depth distribution for monoenergetic electrons, was experimentally determined at 1.21 MeV and 1.66 MeV. These measurements were complemented by Geant4 Monte Carlo simulations to extend the response matrix across the full 0.2 to 4.0 MeV range with a 0.2 MeV step. The simulations accounted for electromagnetic interactions, including multiple scattering, ionization, and bremsstrahlung, and were validated against experimental data, showing good agreement. A key outcome of this work is the determination of the BAS-SR IP plate energy deposition response coefficient for electrons, measured as αe (PSL/MeV), using a 60Co source with varying titanium absorber thicknesses. Unlike prior studies that assumed identical response coefficients for electrons and gamma rays, this work highlights potential differences in coefficients. The experimental and simulated response matrices exhibited consistent signal-depth profiles, with low-energy electrons (＜0.8 MeV) showing a monotonic signal decrease with depth, while higher-energy electrons produced a peak signal at deeper layers due to secondary electron generation. The spectrometer’s upper detection limit was confirmed to be approximately 4.0 MeV, beyond which energy resolution diminishes. The calibrated response matrix enables reliable reconstruction of electron energy spectra in laser-plasma experiments, providing a robust tool for diagnosing hot electron temperatures. The spectrometer’s passive, offline measurement approach eliminates the need for electromagnetic shielding, making it highly adaptable to extreme radiation environments. This work lays a critical foundation for future applications in laser-plasma diagnostics, with potential impacts on advancing ICF, high-energy physics, and related technologies. The combination of experimental calibration and simulation ensures the spectrometer’s accuracy and versatility, offering a valuable resource for researchers studying relativistic laser-matter interactions.